Shoot him if he runs [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2007)
Rogue agent Teddy Fay was long thought dead but, Stone Barrington, Holly Barker and Dino Baldachetti have been sent by the CIA to the St. Marks in the Caribbean to track him down.